The pursuit of the (Latin) American dream in the time of crises: Portugal’s diplomatic and commercial changes towards the region (2005–15) - Fretes Carreras, Luis A.; Moriconi, M. (Portuguese Journal of Social Science, 2018)
To overcome the global crisis, Portugal sought to internationalize its economy. Latin America, a region that grew steadily for a decade, has become a region of interest for the Iberian country. This article analyses the changes to the diplomatic and commercial schemes between both regions and explains how, when, by whom and through which strategies these relations have been modified. While Brazil continues to be the privileged partner, Portugal is strengthening its relationship with new strategic countries, primarily the components of the Pacific Alliance. As a result, the historical negative balance of trade became positive in 2012. The data show greater dynamism in commercial exchanges and political relations in recent years and the incorporation of new political actors designed to stimulate and deepen bilateral relations. Although several authors point to Portugal as a state that promotes economic diplomacy, this article suggests that what has prevailed in strengthening relations with Latin America is a commercial and business diplomacy, leaning heavily on key political actors and ‘anchor’ companies installed in the new markets. The ideological affinity of governments appears to be a determining factor in extending political and commercial ties. As other works have shown, this case study proves a positive correlation between trade/investment state agencies and diplomatic activities and the increase in bilateral trade flows.